2010
DOI: 10.1152/ajpcell.00529.2009
|View full text |Cite
|
Sign up to set email alerts
|

Airborne particulate matter selectively activates endoplasmic reticulum stress response in the lung and liver tissues

Abstract: Airborne particulate matter selectively activates endoplasmic reticulum stress response in the lung and liver tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
170
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(176 citation statements)
references
References 56 publications
5
170
0
1
Order By: Relevance
“…These findings implicating mitochondrial ROS production as the principal source of asbestos-induced free radicals in our model are in accord with our prior studies that include the following: (1) p0-A549 cells lacking mitochondrial DNA and incapable of mitochondrial ROS production, are protected against asbestosinduced DNA damage, p53 activation, and apoptosis (7,8,22); (2) using highly sensitive reduction-oxidation-sensitive green fluorescent proteins targeted to the mitochondria or cytoplasm to detect ROS production, we have previously reported that the mitochondria are the primary source of ROS generation (42); (3) the mitochondria-regulated (intrinsic) death pathway is the primary pathway mediating AEC apoptosis in vitro (7); and (4) a mitochondria-targeted DNA repair protein (8-oxoguanine DNA glycosylase) or mitochondrial aconitase 2 overexpression each prevent oxidant-induced AEC apoptosis, despite high levels of mitochondrial ROS production (42). Our data with asbestosexposed AECs implicating mitochondrial ROS in triggering ER stress also concur with studies showing that antioxidants, including those targeted to the mitochondria, attenuate oxidative stress-induced ER stress and apoptosis in other cell types (30)(31)(32)(33). Mitochondria-targeted antioxidants protect against oxidantinduced ER stress and intrinsic apoptosis of pancreatic beta cells (31,33).…”
Section: Discussionsupporting
confidence: 80%
“…These findings implicating mitochondrial ROS production as the principal source of asbestos-induced free radicals in our model are in accord with our prior studies that include the following: (1) p0-A549 cells lacking mitochondrial DNA and incapable of mitochondrial ROS production, are protected against asbestosinduced DNA damage, p53 activation, and apoptosis (7,8,22); (2) using highly sensitive reduction-oxidation-sensitive green fluorescent proteins targeted to the mitochondria or cytoplasm to detect ROS production, we have previously reported that the mitochondria are the primary source of ROS generation (42); (3) the mitochondria-regulated (intrinsic) death pathway is the primary pathway mediating AEC apoptosis in vitro (7); and (4) a mitochondria-targeted DNA repair protein (8-oxoguanine DNA glycosylase) or mitochondrial aconitase 2 overexpression each prevent oxidant-induced AEC apoptosis, despite high levels of mitochondrial ROS production (42). Our data with asbestosexposed AECs implicating mitochondrial ROS in triggering ER stress also concur with studies showing that antioxidants, including those targeted to the mitochondria, attenuate oxidative stress-induced ER stress and apoptosis in other cell types (30)(31)(32)(33). Mitochondria-targeted antioxidants protect against oxidantinduced ER stress and intrinsic apoptosis of pancreatic beta cells (31,33).…”
Section: Discussionsupporting
confidence: 80%
“…4) Antioxidants, including those targeted to the mitochondria, attenuate oxidative stress-induced endoplasmic reticulum stress and intrinsic apoptosis in AEC as well as other cell types (35)(36)(37). Thus, the levels of oxidative stress-induced AEC mtDNA damage are crucial in triggering a DNA damage response (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that AECs, in their attempt to regenerate the alveolar epithelium after injury, may inherently be under ER stress and UPR activation in their hyperplastic state secondary to intrinsic factors such as increased metabolic demand, thus perpetuating an ongoing injuryremodeling cycle. Finally, exogenous exposures could contribute to ER stress, including herpesviruses, cigarette smoke, and inhaled particulates, all of which have been shown to induce ER stress in lung epithelium (24,25,32,49).…”
Section: Potential Causes Of Er Stress In Ipfmentioning
confidence: 99%